Efficacy and toxicity of drug-loaded nanoparticle using hepato-mimetic microfluidic chip system - 김호영 (The Graduate School, Ajou University, 2022)
The aim of this study is to evaluate the anticancer efficacy of doxorubicin (DOX) and the toxicity of paclitaxel (PTX) according to formulation and cell culture conditions using a biomimetic microfluidic chip system. Using a ROS sensor chip-based biomimetic microfluidic system, HepG2 liver cancer cells were treated with drug-loaded human serum albumin-oleic acid nanoparticles (AONs) in serum-free medium at 37 °C, 5% CO for 24 h. The HepG2 seeded chip was coupled to the microfluidic system. Cell uptake and viability were assessed for free drug (DOX, PTX) and doxorubicin loaded nanoparticles (DOX-AON), paclitaxel loaded nanoparticles (PTX-AON) under static or dynamic conditions (5 dyne/cm2). Intracellular drug uptake was observed using a confocal laser scanning microscope, and cell viability according to drug concentration was evaluated by MTT assay. In addition, the ROS generated in cells treated with free drugs (DOX, PTX) under dynamic conditions was confirmed in a dose-dependent manner using the ROS sensor, and the anticancer efficacy and hepatotoxicity of the drug were evaluated in relation to the cell viability. The efficacy and toxicity of drug-loaded nanoparticles varied in a dose-dependent manner in HepG2 according to the degree of ROS occurrence. Drug-loaded nanoparticles increased intracellular fluorescence intensity and decreased cell viability compared to free drug under dynamic conditions. The IC50 values of DOX were 13.81 ug/mL, 9.77 ug/mL, and 6.026 ug/mL in static, dynamic, and DOX-AONs-treated conditions, respectively. The IC50 values of PTX were 50.53 ug/mL, 38.35 ug/mL, and 20.67 ug/mL in the same order as DOX (static, dynamic, AONs). The concordance rates of cell viability and ROS were 78.95% for DOX and 92.61% for PTX. The sensor chip-based biomimetic microfluidic system was useful to evaluate the real-time efficacy and toxicity of free drugs and drug-loaded AONs on human tissues.
학위논문(석사)--아주대학교 일반대학원 :약학과,2022. 2
Keywords: IC50 value; ROS sensor; anti-cancer efficacy; biomimetic microfluidic system; cell viability; doxorubicin; hepatotoxicity; nanoparticles; paclitaxel